New species of Zenoria Mulsant (Coleoptera: Coccinellidae) from Brazil and Peru - Santos, Paula B.; González F., Guillermo (Zootaxa, 2016)
Four new species of Zenoria Mulsant, 1850 are described: Zenoria limitrophi sp. nov. from Brazil; and Z. westerduijni sp. nov., Z. carbo sp. nov., and Z. miroi sp. nov. from Peru. Diagnostic characters are illustrated and relationships with previously described species are discussed.